Natural Course of Spontaneous Pneumothorax without Bullae or Blebs under High-Resolution Computed Tomography - Kim, Jung Tae; Oh, Tae Yoon; Chang, Woon Ha; Kong, Joon Hyuk; Baek, Kang Seok; Lee, Won Jin; Bang, Yun Yi (The Thoracic and Cardiovascular Surgeon, 2014)
Background The cause of primary spontaneous pneumothorax (PSP) is known as rupture of some bullae or blebs.Objective The aim of this study is to clarify the natural course of spontaneous pneumothorax in the absence of bullae or blebs under high-resolution chest computed tomography (HRCT).Patients and Method From January 2006 to December 2010, 854 patients with PSP were enrolled in the study group. All subjects received a chest CT scan and were reviewed retrospectively.Result There were 56 PSP cases (6.5%) without bullae or blebs under HRCT. Treatments included oxygen therapy in 16 (28.5%) cases, arrow catheter insertion in 22 (39.2%) cases, closed thoracostomy in 17 (30.3%) cases, and 1 (1.7%) case received a video-assisted thoracoscopic surgery (VATS) operation. There were nine recurrent cases (16%). Of the nine cases, eight cases were treated with VATS operation. Several bullae or blebs were found in five of those nine operated cases, and there were severe inflammatory fibrotic changes on the apex of one of the nine operated cases.Conclusion Several bullae and blebs were revealed upon operation of PSP without previously detected bullae and blebs on HRCT. We cautiously recommend operating on PSP regardless of whether bullae and blebs are detected by HRCT as long as there are no contraindications to the operation.
Keywords: pneumothorax; computed tomography; thoracoscopy